2006
DOI: 10.1002/cbf.1328
|View full text |Cite
|
Sign up to set email alerts
|

The potential antioxidant effect of raloxifene treatment: a study on heart, liver and brain cortex of ovariectomized female rats

Abstract: The antioxidant activity of some compounds buffer the free radicals generated either endogenously or exogenously, thus decreasing the potential damage mediated by oxidation. Recent studies documented that raloxifene has antioxidant properties in vitro. However, there are limited animal studies available to show raloxifene's antioxidant properties. We aimed to investigate the effects of raloxifene on antioxidant enzymes such as SOD, CAT and GPX, TrxR and the levels of GSH and MDA in heart, liver and brain corte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 40 publications
(32 reference statements)
2
27
0
Order By: Relevance
“…Bilateral ovariectomies were performed under intraperitoneally administered ketamine and xylazine HCl anesthesia using a dorsal approach in all animals; the rats were kept for 1 month to recover and adapt to the absence of endogenous estrogen. The 1-month duration for ovariectomized animals was previously used in the same experimental model successfully, and it has been reported that this protocol produced postmenopausal changes in ovariectomized animals [27,28].…”
Section: Animalsmentioning
confidence: 97%
“…Bilateral ovariectomies were performed under intraperitoneally administered ketamine and xylazine HCl anesthesia using a dorsal approach in all animals; the rats were kept for 1 month to recover and adapt to the absence of endogenous estrogen. The 1-month duration for ovariectomized animals was previously used in the same experimental model successfully, and it has been reported that this protocol produced postmenopausal changes in ovariectomized animals [27,28].…”
Section: Animalsmentioning
confidence: 97%
“…RAL improves the endothelial function in ovariectomized (OVX), aged, or hypertensive rats, ameliorates the hypertension-induced endothelial dysfunction by reducing the production of reactive oxygen species, and enhances endothelial nitric oxide- (NO-) dependent vasodilatation in vitro. Moreover, RAL causes direct vasodilatation [15]. It reduces the increased cardiovascular risk in patients with osteoporosis, although the outcomes of the RUTH trial showed that RAL did not affect the overall risk of coronary heart disease in elderly women.…”
Section: Introductionmentioning
confidence: 99%
“…Intracellular GSH is converted into GSSG by glutathione peroxidase, which catalyzes the reduction of H 2 O 2 and various hydroperoxides. Konyalioglu et al [51] reported that raloxifene (another selective estrogen receptor modulator) treatment significantly increases the levels of GSH in brain and heart tissues of ovariectomized females although no significant differences are found in liver tissue.…”
Section: Discussionmentioning
confidence: 96%